Authenticity traditional costume of Zapin symbolize wealth in the art of a culture in Johor / Khairi Asyraf Abdul Karim and Dayang Intan Farahanies Almurid - Abdul Karim, Khairi Asyraf; Almurid, Dayang Intan Farahanies (2022)
In the current modernization, Baju Melayu and Baju Kurung now only remain as formal attire forsome occasions because it is more polite, according to the events attended. Each state has its designs and silhouettes of traditional costume. In line with the changing times, now various fashion shows and modern designs have been accepted by society. This is one of the reasons for the change in Baju Melayu and Baju Kurung that is happening now as an example of traditional to contemporary such as Baju Melayu Hipster and Baju Kurung Modern. As a result, Baju Melayu has now changed to Kurta and Baju Kurung has changed to Tunic. This makes traditional costume no longer as original as it used to be which symbolizes Malaysian identity. As Malaysians, they should maintain these traditional costumes with original designs and preserve them as a continuation of our ancestors to future generations. Now, Baju Melayu and Baju Kurung are no longer worn with a complete set. This is also due to the elements of modernization of global culture that have a wide influence. The mass media became a priority to make it happen quickly and widely.